Hadoop for dummies - DeRoos, Dirk; Zikopoulos, Paul C; Melnyk, Roman B; Brown, Bruce; Coss, Rafael (New Delhi: Wiley India Pvt. Ltd., 2019)
The text understand the value of big data and how Hadoop can help manage it navigate the Hadoop 2 ecosystem and create clusters use applications for data mining, problem-solving, analytics and more.
Keywords: Computer Science Engineering; Hadoop; Hadoop cluster; Big data; Data; Database